A rational approach to identifying newborns with hearing loss caused by congenital cytomegalovirus infection by dried blood spot screening. (3rd August 2018) - Moteki, Hideaki; Isaka, Yuichi; Inaba, Yuji; Motobayashi, Mitsuo; Nishio, Shin-Ya; Ohira, Satoshi; Yano, Takuya; Iwasaki, Satoshi; Shiozawa, Tanri; Koike, Kenichi; Usami, Shin-Ichi
Abstract: Objective: Congenital cytomegalovirus (cCMV) infection is the most common congenital infection, with the majority of infected newborns having no detectable signs. The aim of this study was to examine the accuracy of our newly developed DBS-based assay as an appropriate mass screening method for cCMV infection. Methods: Between May 2011 and October 2016, newborns delivered at six hospitals in Nagano Prefecture, Japan were enrolled prospectively. We employed dried blood spot (DBS)-based assays with real-time quantitative PCR (qPCR). Results: Prior to the clinical study, confirmation analysis was carried out using positive and negative controls. The sensitivity and specificity of this DBS-based qPCR assay for the detection of CMV DNA were 83 and 97%, respectively. During the study period, 9675 newborns were enrolled. The total recovery rate of DBS was 99.92% (9, 667/9, 675). From our analysis of the 9, 667 samples, 47 DBS samples were found positive by the qPCR test (0.48%), and 9620 (99.5%) DBS samples were CMV-negative. Conclusions: The risk of neural disorders associated with cCMV infection is thought likely to increase with CMV viral load in the blood. DBS screening for cCMV may be sufficient in a clinical setting, and offers a realistic and feasible option for universal mass screening.